The influence of residual apixaban on bleeding complications during and after catheter ablation of atrial fibrillation. Issue 5 (28th July 2017) - Mukai, Yutaro; Wada, Kyoichi; Miyamoto, Koji; Nakagita, Kazuki; Fujimoto, Mai; Hosomi, Kouichi; Kuwahara, Takeshi; Takada, Mitsutaka; Kusano, Kengo; Oita, Akira
Abstract: Background: The periprocedural protocol for atrial fibrillation (AF) ablation commonly includes anticoagulation therapy. Apixaban, a direct oral anticoagulant, is currently approved for clinical use; however, little is known about the effects of residual apixaban concentration on bleeding complications during/after AF ablation. Therefore, we measured residual apixaban concentration by using mass spectrometry and examined the anticoagulant's residual effects on bleeding complications. Methods: Fifty‐eight patients (Mean age of 64.7±12.5 years; 31 males, 27 females) were enrolled and administered apixaban twice daily. We analyzed trough apixaban concentration, activated clotting time (ACT), heparin dose, and bleeding complications during/after AF ablation. Apixaban concentrations were directly measured using mass spectrometry. Results: Bleeding complications were observed in 19 patients (delayed hemostasis at the puncture site, 16; hematuria, 3; hemosputum, 1). No patient required blood transfusion. The mean trough apixaban concentration was significantly lower in patients with bleeding complications than without (152.4±73.1 vs. 206.8±98.8 ng/mL respectively, P =0.037), while the heparin dose to achieve ACT>300 s was significantly higher in patients with bleeding complications (9368.4±2929.0 vs. 7987.2±2135.2 U/body respectively, P =0.046). Interestingly, a negative correlation was found between the trough apixaban concentration and the heparin dose to achieve ACT>300 s ( P =0.033, R=‐0.281). Conclusions: Low residual plasma apixaban is associated with a higher incidence of bleeding complications during/after AF ablation, potentially because of a greater heparin requirement during AF ablation.